Effects of nandrolone decanoate and resistance exercise on skeletal muscle in adult male rats - Dela Cruz, Cynthia; Agati, Leandro B. [UNESP]; Pereira, Oduvaldo C. M. [UNESP] (Soc Chilena Anatomia, 2012)
The aim of this study was to compare the effects of resistance exercise associated or not with nandrolone decanoate (ND) on skeletal muscles and body mass of adult male rats. Training protocol consisted of 15 jump sessions, for 6 weeks. ND (5mg/kg) was administered twice a week. The exercise was effective in inducing respective enlargements in fiber areas of extensor digitorum longus and soleus muscles. ND associate with exercise was also able to induce increases in fiber areas these muscles. In untrained group that received nandrolone decanoate an improved in muscular parameters could be observed. In conclusion, the resistance exercise was able to promote an enlargement in fiber areas of both muscles studied without ND treatment, indicating that after a period of time of adaptation to exercise, the muscular effects caused by ND could be achieved in the same way by exercise, without ND and without risks for health.

El objetivo de este estudio fue comparar los efectos del ejercicio de resistencia con o sin decanoato de nandrolona (DN) en el músculo esquelético y la masa corporal de ratas macho adultas. El protocolo de entrenamiento consistió en 15 sesiones durante 6 semanas de saltos. DN 5mg/kg se administró dos veces durante la semana. El ejercicio fue efectivo para inducir un aumento en el área de las fibras de los músculos extensor largo de los dedos y sóleo. El DN asociado con el ejercicio fue capaz de inducir un aumento en el área de las fibras de los músculos. En el grupo de DN sin entrenamiento, se observó un aumento en los parámetros musculares evaluados. El ejercicio de resistencia sin DN fue capaz de promover un aumento en el área de las fibras de los músculos, lo que indica que después de un período de adaptación al ejercicio, el efecto en los músculos causada por la DN se logró por el ejercicio, sin una gestión DN y los consiguientes peligros para la salud.
Efectos del decanoato de nandrolona y el ejercicio de resistencia en el músculo esquelético de ratas machos adultos
Keywords: Anabolic Androgenic Steroids; Extensor Digitorum Longus; Nandrolone Decanoate; Resistance Training; Skeletal Muscles; Soleus